Congestion mitigation using UPFC - Arun Kumar Reddy K.; Singh S.P. (My University, 2025)
Transmission congestion is one of the most challenging issues in operation of deregulated electricity markets of today. This study investigates into benefit of unified power flow controller (UPFC) as a viable solution to the problem of congestion management. A comprehensive load flow model for the UPFC is presented which has the capability to control active and reactive powers and voltage magnitude simultaneously. This study discusses about two different approaches for determination of suitable location of UPFC. One of them is sensitivity-based approach and the other is pricing-based method. Reduction in total system losses has been taken as objective in sensitivity-based approach. Furthermore, sensitivity of total system losses with respect to control parameters of UPFC have been evaluated using two different methods. A pricing-based approach which makes use of locational marginal price difference and congestion rent for determination of suitable location of UPFC. Minimisation of cost of rescheduling subjected to system operating constraints is the objective to be met for congestion management. Interior point method, a mathematical tool for non-linear optimisation, is used to obtain the solution of above-mentioned problem. © The Institution of Engineering and Technology 2016.